Ion-plasma deposition of thin quasicrystalline Al-Cu-Fe and Al-Cu-Co films - Ryabtsev, S.I.; Sukhova, O.V. (Вопросы атомной науки и техники, 2020)
Al-Cu-Fe and Al-Co-Cu thin films were firstly deposited on sodium chloride or glass-ceramic substrates by modernized method of three-electrode ion-plasma sputtering. The nominal compositions of the films were chosen in the regions of quasicrystalline phases formation. The as-sputtered films were typically 85 to 260 nm thick. The films were annealed at temperatures ranging from 873 to 923 K for 10 min…3 h. The structure of films was studied by scanning and transmission electron microscopy and X-ray analysis. Electrical properties were determined by a fourprobe method. The as-deposited Al-Cu-Fe film was found to consist of isolated quasicrystalline nanoparticles of icosahedral i-phase. With substitution of Fe for Co in Al-Co-Cu film, X-ray amorphous phase and only traces of quasicrystalline decagonal D-phase were revealed. After annealing, the films were predominately quasicrystalline due to transformation of metallic phases into quasicrystalline. At the same time, the size of coherent scattering regions for quasicrystals increased by two times from ⁓ ~ 3 to 6 nm. Measurements of electrical resistivity showed that no phase transformations occurred in Al-Cu-Fe film up to 723 K and in Al-Co-Cu film up to 640 К. With following increase in temperature, electrical resistivity of Al-Cu-Fe film increased by six orders of magnitude (up to 6∙10⁷ Ω/sq). In contrast, electrical resistivity of Al-Co-Cu film decreased by ⁓ ~ 2 times. After cooling to room temperature, resistivity of Al-Cu-Fe film equaled to ~ 3∙10⁵ Ω/sq and that of Al-Co-Cu film – to 8.7 Ω/sq. We concluded that Al-Cu-Fe thin film is more suitable candidate for application as precise high-ohmic materials. Тонкі плівки Al-Cu-Fe та Al-Co-Cu були вперше нанесені на підкладки з натрій хлориду та сіталу модернізованим методом триелектродного іонно-плазмового осадження. Номінальний склад плівок обирали в області існування квазікристалічних фаз. Товщина напилених плівок складала від 85 дo 260 нм. Плівки відпалювали в інтервалі температур 87…923 K на протязі 10 хв…3 год. Структуру плівок вивчали методами скануючої і трансмісійної електронної мікроскопії та рентгеноструктурного аналізу. Електричні властивості визначали чотиризондовим методом. Встановлено, що в свіжонапиленому стані плівка Al-Cu-Fe складається з ізольованих квазікристалічних наночастинок ікосаедричної i-фази. У разі заміни Fe на Co в плівці Al-Co-Cu виявлені рентгеноаморфна фаза і сліди квазікристалічної декагональної D-фази. Після відпалу плівки мають переважно квазікристалічну структуру внаслідок перетворення металевих фаз на квазікристалічні. При цьому розмір областей когерентного розсіювання квазікристалів збільшується в два рази з ~ 3 до 6 нм. Виміри електричного опору показали, що в плівці Al-Cu-Fe відсутні фазові перетворення аж до температури 723 K, а в плівці Al-Co-Cu – до 640 К. Під час наступного нагріву електричний опір плівки Al-Cu-Fe збільшується на шість порядків (до 6∙10⁷ Ом/кв). Навпаки, електричний опір плівки Al-CoCu зменшується в ~ 2 рази. Після охолодження до кімнатної температури опір плівки Al-Cu-Fe складає ~ 3∙10⁵ Ом/кв, а плівки Al-Co-Cu – 8,7 Ом/кв. Зроблено висновок, що плівка Al-Cu-Fe є більш перспективним матеріалом для виготовлення прецизійних високоомних резисторів. Тонкие пленки Al-Cu-Fe и Al-Co-Cu были впервые нанесены на подложки из натрий хлорида и ситала модернизированным методом трехэлектродного ионно-плазменного осаждения. Номинальные составы пленок выбирали в области существования квазикристаллических фаз. Толщина напыленных пленок составляла от 85 дo 260 нм. Пленки отжигали в интервале температур 873…923 K в течение 10 мин…3 ч. Структуру пленок изучали методами сканирующей и трансмиссионной электронной микроскопии и рентгеноструктурного анализа. Электрические свойства определяли четырехзондовым методом. Установлено, что в свеженапыленном состоянии пленка Al-Cu-Fe состоит из изолированных квазикристаллических наночастиц икосаэдрической i-фазы. При замене Fe на Co в пленке Al-Co-Cu обнаружены рентгеноаморфная фаза и следы квазикристаллической декагональной D-фазы. После отжига пленки имеют преимущественно квазикристаллическую структуру вследствие превращения металлических фаз в квазикристаллические. При этом размер областей когерентного рассеяния квазикристаллов увеличивается в два раза с ~ 3 до 6 нм. Измерения электрического сопротивления показали, что в пленке AlCu-Fe отсутствуют фазовые превращения вплоть до температуры 723 K, а в пленке Al-Co-Cu – до 640 К. При последующем нагреве электрическое сопротивление пленки Al-Cu-Fe возрастает на шесть порядков (до 6∙10⁷ Ом/кв). Напротив, электрическое сопротивление пленки Al-Co-Cu уменьшается в ~ 2 раза. После охлаждения до комнатной температуры сопротивление пленки Al-Cu-Fe составляет ~ 3∙10⁵ Ом/кв, а пленки Al-Co-Cu – 8,7 Ом/кв. Сделан вывод о том, что пленка Al-Cu-Fe является более перспективным материалом для изготовления прецизионных высокоомных резисторов.